2020
DOI: 10.1042/bsr20191203
|View full text |Cite
|
Sign up to set email alerts
|

Promoter polymorphisms in the lncRNA-MIAT gene associated with acute myocardial infarction in Chinese Han population: a case–control study

Abstract: Background: Coronary atherosclerotic disease (CAD) is one of the greatest causes of death and disability around the world, and has emerged as a major public health problem. Acute myocardial infarction (AMI) is the most serious type of CAD. Myocardial infarction (MI) association transcript (MIAT) has demonstrated that it plays an important role in AMI. Purpose: To investigate the association between MIAT promoter polymorphisms and AMI in Chinese Han population. Methods: A total of 212 AMI patients and 218 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Recently, Ma et al investigated ten polymorphisms of MIAT promoters and found that two SNPs (rs5752375T/C and rs9608515T/C) were associated with MI, with the TT genotype being a risk factor compared with the CC genotype, potentiating the role of MIAT SNPs in CAD development [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Ma et al investigated ten polymorphisms of MIAT promoters and found that two SNPs (rs5752375T/C and rs9608515T/C) were associated with MI, with the TT genotype being a risk factor compared with the CC genotype, potentiating the role of MIAT SNPs in CAD development [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the functional role of MIAT polymorphisms might be related to gene expression alteration. A minor allele at exon 5 11,741 G>A SNP of MIAT increased its transcription compared with major allele G. Additionally, rs5752375 and rs9608515 polymorphisms of MIAT promotor might influence binding of the transcription factors, causing it to lose some and interact with others [ 31 , 32 ]. MIAT was highly expressed in the atheromatous plaques [ 33 ] and the peripheral blood of CAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA SMILR seems to play a role in plaque stability [58], and its plasma levels positively correlate with C-reactive protein [59]. SNPs in the lncRNA MIAT promoter correlated with acute myocardial infarction in a Chinese Han population [86], while a specific polymorphism in MALAT1 (rs619586AG/GG) might be CVD protective [87].…”
Section: Lncrnas As Biomarkers In Atherosclerosismentioning
confidence: 99%
“…While the previous study focused on the SNPs within the GOMAFU transcript, another study analyzed whether SNPs near the GOMAFU transcript were associated with acute myocardial infarction (AMI) [ 137 ]. This study examined the proximal promoter region of GOMAFU through PCR amplification using genomic DNA isolated from the peripheral leukocytes of controls and AMI patients in a Chinese Han population.…”
Section: Discovery Of Gomafu and Disease-associate...mentioning
confidence: 99%
“…This study examined the proximal promoter region of GOMAFU through PCR amplification using genomic DNA isolated from the peripheral leukocytes of controls and AMI patients in a Chinese Han population. Comparing the SNPs identified from the control and patient group, two SNPs were significantly associated with AMI, rs5752375, and rs9608515 ( Table 1 and Figure 2 ) [ 137 ]. These two SNPs are located 938 and 864 bp upstream of the GOMAFU transcription start site, respectively, likely within the GOMAFU promoter.…”
Section: Discovery Of Gomafu and Disease-associate...mentioning
confidence: 99%